O processo de institucionalização de redes cooperativas de pesquisa : um estudo na Cooperativa Central de Pesquisa Agrícola - COODETEC - Silva, Fabrízio Meller da (2009)
The area of Science and Technology (S&T) has been having alterations throughout the last decades. This fact has been influencing the organizations, the public as well as the private ones, in the application of its strategies and organizational structures, mainly in its activities of researches. Therefore, new organizational configurations have been adopted by the institutes of research in Brazil, the cooperative network of research. In this context, the purpose of this piece of work is to describe how the institutionalization process of the formation of cooperative network of research has occurred in the COODETEC - Central Cooperative of Agriculture Research. Regarding to the methodological procedures, the research has characterized as qualitative, descriptive, and sectional with longitudinal perspective. For this semi-structured interviews have been done with some leaders/researchers of COODETEC for the collection of primary data and the documental research for the collection of secondary data. The interpretation of the collected material has allowed the conclusion that the cooperative network of research has become a model adopted by COODETEC since its creation.